Community-Based Coral Reef Conservation In The Kepulauan Seribu - Donny Juliandri Prihadi; Meera Gupta; Priya Patel (Journal of Multidisciplinary Sustainability Asean, 2025)
Background. The coral reef ecosystems of Kepulauan Seribu National Park, crucial for marine biodiversity and local livelihoods, face severe anthropogenic pressures from coastal development and tourism. Community-Based Conservation (CBC) has emerged as a vital strategy to counteract this degradation, yet its specific impacts in this high-pressure marine area require rigorous evaluation. Purpose. This research evaluates the ecological efficacy and socioeconomic contributions of established CBC programs in Kepulauan Seribu. The study investigates the key factors influencing successful community participation and the resulting impacts on coral reef health. Methods. A mixed-methods approach was employed, integrating quantitative ecological surveys with qualitative socioeconomic analysis. Ecological data were collected via Line Intercept Transects (LIT) at multiple CBC-managed sites and non-CBC (control) sites. Socioeconomic data were gathered through semi-structured interviews (n=120) with community members, program managers, and local stakeholders. Results. The findings indicate that CBC-managed reefs exhibited significantly higher live coral cover and greater reef fish biomass compared to control sites. Socioeconomic analysis revealed enhanced community stewardship, supplementary income streams, and increased environmental awareness. However, institutional challenges, particularly funding instability and policy conflicts with tourism development, were identified as persistent obstacles. Conclusion. Community-based conservation demonstrates tangible success in mitigating reef degradation in Kepulauan Seribu. This study concludes that while CBC is effective, its long-term sustainability hinges on strengthening institutional support, resolving resource-use conflicts, and ensuring equitable benefit sharing for participating communities.